Economic impact of digital dermatitis, foot rot, and bovine respiratory disease in feedlot cattle. Issue 2 (19th May 2021) - Cortes, Julian Alberto; Hendrick, Steve; Janzen, Eugene; Pajor, Ed A; Orsel, Karin
Abstract: Digital dermatitis (DD ) has emerged in North American feedlots, although production and economic impacts are not fully understood. Objectives of this study were to: (1) estimate the economic impact of a single case of DD, foot rot (FR ), and bovine respiratory disease (BRD ) in feedlot cattle and (2) determine its impact on average daily gain (ADG ). Feedlot cattle health and production records were available from two feedlots for a 3-yr interval. The dataset consisted of 77, 115 animal records, with 19.3% (14, 900) diagnosed with a disease. Diseased animals were categorized into five groups: DD, FR, BRD, other diseases (OT), and two or more diseases (TM), with a treatment cumulative incidence of 6.0%, 59.1%, 10.7%, 12.7%, and 11.5%, respectively. FR was the disease with the highest cumulative incidence in both heifers and steers (58.8% and 59.6%, respectively). Of all fall-placed cattle diagnosed with any disease, 48.1% of the cases were FR. DD affected the partial budget in five out of the eight groups of cattle, with the highest impact of DD seen in grass yearling heifers and grass yearling steers: $-98 and $-96 CAD, respectively, relative to their healthier counterparts. Healthy cattle had a significantly higher ADG when compared with DD cattle in five of the eight categories, ranging from 0.11 kg/d in winter-placed heifers to 0.17 kg/d in fall-placed steers. In the economic analysis, it was concluded that on an individual animal basis, BRD was the most impactful of all analyzed diseases, whereas DD was second, marking the importance of controlling and mitigating this foot condition. Identifying differential effects of diseases on a partial budget analysis and ADG of the types of cattle stratified by sex enables feedlot producers to focus control and mitigation strategies on specific groups.